IMPLEMENTATION OF ADIWIYATA PROGRAM IN SUPPORTING ESTABLISHMENT OF ENVIRONMENT CARES CHARACTER IN 4 PUBLIC HIGH SCHOOL PANDEGLANG - Fathurahman, Mohammad Dendy (Indonesia University of Education, 2017)
The environmental damage has touched fundamental aspects as the impact of the error of looking at the relationship between humans and the environment. Different views of humans have made the environment as objects that need to be exploited as much as possible, regardless of the impact and sustain of other living creatures. Along with the increasing complexity of environmental issues become increasingly important and urgent to publish the environmental movement in the context of education, so that later gave birth to the concept of green and green school curriculum in various parts of the world. The study of the important role of the Adiwiyata program in shaping the character of care for the environment is still very weak. The lack of publicity about the Adiwiyata program who actually can play a role in shaping the character of environmental care. The fact is the reason for the need to do research to uncover the reality of the implementation of the program and the role of the character Adiwiyata environmental awareness of students in the school. The objective to describe implements selected Adiwiyata program in support of the formation of character concerned about the environment in SMAN 4 Pandeglang. The method used in this research is a qualitative descriptive method. The research result shows that the implementation of the program Adiwiyata has a role in supporting the formation of character concerned lingkuungan students in school.